(untitled) (Psychology Travelogs, 2024)
The article discusses the theoretical aspects of psychological rehabilitation of people who have experienced traumatic events. The author of the article defines the content of the concepts of ‘rehabilitation’, ‘psychological rehabilitation’, and ‘traumatic event’. The article describes the purpose, main tasks, and principles of psychological rehabilitation of people who have experienced traumatic events. The author of the article argues that solving the main tasks of psychological rehabilitation of people who have experienced traumatic events is possible only on the basis of a deep diagnosis of mental changes in a person, as well as the study of socio-psychological factors that influenced his or her mental state in different periods of illness. The article reveals that a traumatic event is characterised by suddenness, destructive force, intensity and leads to mental trauma. In view of this, the article describes the stages of psychologist’s work on psychological rehabilitation of a person who has experienced a traumatic event. Psychological rehabilitation of people who have experienced traumatic events is carried out in several stages: the diagnostic stage, which aims to identify mental changes in a person at all stages of the disease and to study the socio-psychological factors that affected their mental state; the stage of rehabilitation, the main task of which is to prevent the formation of a person’s socio-psychological defect; the stage of rehabilitation, which is aimed at mastering the person’s socio-psychological skills of adaptation to the conditions of the social environment; the rehabilitation stage, which involves taking measures to improve social and living conditions and work activities. The author of the article concludes that psychological rehabilitation of survivors of traumatic events requires a specialist to have a qualified psychological training, a highly developed personal and professional identity, humanistic orientation, etc. The author considers the prospects for further developments in this area in the definition and empirical study of personal and professional qualities of psychologists to work with people who have experienced traumatic events.